Application of a Novel Film Sealant Technology for Penetrating Corneal Wounds: An Ex-Vivo Study - Jackie Tan; Leslie John Ray Foster; Stephanie Louise Watson (Applied Sciences, 2020)
Aim: To compare the burst pressures of corneal wounds closed with a laser-activated, chitosan-based thin film adhesive against self-seal, sutures and cyanoacrylate. Methods: 2, 4 or 6 mm penetrating corneal wounds were created on 100 freshly enucleated bovine eyes. The wounds were closed using a laser-activated chitosan adhesive (n = 30), self-sealed (control) (n = 30), sutures (n = 20) or cyanoacrylate glue (Histoacryl®) (n = 20). The corneoscleral rim was dissected and mounted onto a custom burst pressure testing chamber. Water was pumped into the chamber at 9ml/hr. The fluid pressure prior to wound leakage was recorded as the ‘burst pressure’. Results: The burst pressure for the 2, 4 and 6 mm wounds were 239.2 mmHg (SD = ±102.4), 181.7 mmHg (SD = ±72.8) and 77.4 mmHg (SD = ±37.4) (p < 0.00001), respectively, for chitosan adhesive. Burst pressure was 36.4 mmHg (SD = ±14.7), 4.8 mmHg (SD = ±4.9) and 2.7 mmHg (SD = ±1.3) (p < 0.00001), respectively, for the self-sealed group. For 4 and 6mm wounds, burst pressures with sutures were 33.0 mmHg (SD = ±19) and 23.5 mmHg (SD = ±17.4) (p = 0.0087), respectively. For cyanoacrylate, burst pressures for 2 and 4 mm wounds were 698 mmHg (SD = ±240.3) and 494.3 mmHg (SD = ±324.6) (p = 0.020087), respectively. Conclusion: This laser-activated chitosan-based adhesive sealed bovine corneal wounds up to 6 mm in length. Burst pressure was higher for the adhesive than sutured or self-sealed wounds, but lower than for cyanoacrylate.